ليلة القدر في الأدب التركي مختارات من الشعر الديواني وشعر التنظيمات - مصطفى محمد شوقي زهران (Maǧallaẗ Kulliyyaẗ Al-ādāb Ǧāmiʿaẗ Būrsaʿīd, 2025)
إن لشهر رمضان بصفةٍ عامة، وليلة القدر بصفة خاصة أهميةً كبرى عند المسلمين كافة، فرمضان هو الشهر الذي نزل فيه القرآن الكريم؛ ذلك الكتاب السماوي المقدس للمسلمين، كما أن للشهر الكريم أفضليةً على بقية الشهور، وفيه ليلةٌ خيرٌ من ألف شهر، وهي الليلة التي نزل فيها القرآن الكريم على رسولنا صلى الله عليه وسلم، يتحراها المسلمون في العشر الأواخر من شهر رمضان، ويجتهدون فيها في العبادة والطاعة، إذ هي ليلة تقدر فيها الآجال والأرزاق، ولأهمية شهر رمضان وليلة القدر عند المسلمين وعظم قدرهما، انعكس ذلك على الأدب الإسلامي، ومنه الأدب التركي، فنظم الشعراء قصائد خاصة بشهر رمضان أسموها (الرمضانية)، كانوا يذكرون فيها فضائل شهر رمضان وقدسيته، ويدرجون في تلك القصائد أبياتًا مخصوصة عن ليلة القدر، وكان توظيف ليلة القدر في الشعر التركي من باب إظهار فضائل تلك الليلة وقدسيتها، ومن باب الدعاء للغير ببلوغ تلك الليلة لتحقيق السعادة الدنيوية والأخروية، أو من باب تشبيه الحبيب بليلة القدر، من حيث صعوبة وصال الحبيب، كما هو الحال في صعوبة بلوغ ليلة القدر. وقد تناولت في هذا البحث مختاراتٍ من دواوين شعراء الديوان وفترة التنظيمات، التي تناولت ليلة القدر، مع ترجمتها إلى العربية وتحليلها أدبيًا وبلاغيًا.The month of Ramadan, in general, and the Night of Qadr, in particular, hold great significance for all Muslims. This blessed month is distinguished above all other months, and within it lies a night better than a thousand months: the Night of Qadr, during which the Qur’an was revealed to our Prophet (peace be upon him). Due to the importance of Ramadan and the Night of Qadr for Muslims, this significance has been reflected in Islamic literature, including Turkish literature. Poets composed special poems dedicated to Ramadan, known as Ramadanîyya, in which they highlighted the virtues and sanctity of this holy month. These poems often included specific verses about the Night of Qadr. The use of the Night of Qadr in Turkish poetry served to emphasize its virtues and sacredness, to offer prayers for others to witness this night and achieve both worldly and eternal happiness, or to compare the beloved to the Night of Qadr, drawing a parallel between the difficulty of uniting with the beloved and the rarity of experiencing the Night of Qadr. In this study, I have explored selections from the divan poetry and Tanzimat period poetry that address the Night of Qadr.